Automating Camera Management for Lecture Room Environments - Cadiz, JJ; Gupta, Anoop; Liu, Qiong; Rui, Yong (2000)
Given rapid improvements in network infrastructure and streaming-media technologies, a large number of corporations and universities are recording lectures and making them available online for anytime, anywhere access. However, producing high-quality lecture videos is still labor intensive and expensive. Fortunately, recent technology advances are making it feasible to build automated camera management systems to capture lectures. In this paper we report on our design, implementation and study of such a system. Compared to previous work—which has tended to be technology centric—we started with interviews with professional video producers and used their knowledge and expertise to create video production rules. We then targeted technology components that allowed us to implement a substantial portion of these rules, including the design of a virtual video director. The system’s performance was compared to that of a human operator via a user study. Results suggest that our system’s quality is close to that of a human-controlled system. In fact, most remote audience members could not tell if the video was produced by a computer or a person.